2020
DOI: 10.21608/aasj.2020.39213.1029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting methods and irrigation intervals on productivity of some bread wheat cultivars

Abstract: A field experiment was carried out at Experimental Farm, in Alkalahyn, Al -Hajer village, Qeft, Qena governorate, Egypt during 2017/2018 and 2018/2019 seasons, to evaluate of three planting methods (Drilling, broadcasting and furrows) and three irrigation intervals (21 , 28 and 35 days) on productivity of three wheat cultivars ( Sids 12 -Misr 2 and Giza 168 ). The results showed that exposing wheat plants to drought stress by increasing irrigation intervals significantly decrease (1000-grain weight, grains spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Finally, the Shandawel-1 cultivar scored the highest yield of 5.22 ton ha -1 compared to other cultivars i.e., Giza-171, Misr-1, and Sakha-94 (Gad et al, 2020). Similar results were reported by Said and Abd El-Moneem (2016); Makarem et al (2019);Al-Zahy et al (2020); Mohammed et al (2021); Mohamed et al (2022) and Upadhyaya and Bhandari, (2022) who reported that superiority any cultivar may be due to the reacting among genetic-make up and their environmental conditions.…”
Section: Wheat Cultivars Performancesupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, the Shandawel-1 cultivar scored the highest yield of 5.22 ton ha -1 compared to other cultivars i.e., Giza-171, Misr-1, and Sakha-94 (Gad et al, 2020). Similar results were reported by Said and Abd El-Moneem (2016); Makarem et al (2019);Al-Zahy et al (2020); Mohammed et al (2021); Mohamed et al (2022) and Upadhyaya and Bhandari, (2022) who reported that superiority any cultivar may be due to the reacting among genetic-make up and their environmental conditions.…”
Section: Wheat Cultivars Performancesupporting
confidence: 86%
“…Furthermore, enough irrigation water may help the plant to absorb its need for water and nutrients as well as increased the grain-filling period (El-Hendawy, 2016). Drought stress leads to decreased fresh and dry matter production (Gora et al, 2022), total chlorophyll, and photosynthesis (Shalaby et al, 2020), and thus reduced the spike length (Kanwal et al, 2020), flag leaf area (El-Sarag and Ismaeil, 2013), grains weight spike -1 and 1000-grain weight (Al-Zahy et al, 2020 andKotb et al, 2021), grain yield (El-Nagar and EL-Gohary, 2022), and increased WUE (Taha et al, 2017). Xu et al (2016) cleared that the increase in WUE was produced from 60 mm water applied at elongation, attaining a relatively high grain yield, whereas enough irrigation with180 mm water applied increased grain yield but decreased WUE.…”
Section: Effect Of Irrigation Intervalsmentioning
confidence: 99%
“…Wheat plants obtained from the planting method by drilling gave the higher mean values of protein (12.32 and 12.37%), wet gluten (33.15 and 33.46%) and dry gluten (10.91 and 11.03%) in the first and second seasons, respectively. The positive influence was observed by the drilling method may be mainly due to uptake of N and cumulating of Co 2 accrue to excellent plant distribution in the field (Al-Zahy et al, 2020). In the same table, hectoliter weight was affected significantly by sowing methods.…”
Section: Effect Of Sowing Methodsmentioning
confidence: 72%
“…Several researchers found that wheat sown by drilling method gave the highest values for plant height, number of tillers m -2 , number of spikes m -2 , number of spikelets spike -1 , number of grains spike -1 , spike length, grain weight spike -1 , 1000-grain weight, straw yield, grain yield and protein percentage compared to the other sowing methods (Chauhdary et al, 2016;Khatri et al, 2019;Al-Zahy et al, 2020;Bakhsh et al, 2020;Singh et al, 2020;Hassanein et al, 2020;Tamirat & Mekides, 2020). Latif et al (2018) concluded that poor results were obtained in the method of broadcast single 1 as compared to the other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Water scarcity in irrigated agriculture, inadequate irrigation, and infrequent rainfall all contribute to water deficit stress (Ouda et al, 2020). Al-Zahy et al (2020) reported that increasing irrigation intervals expose wheat plants to drought stress which can decrease grains spike weight, number of spikes/m 2 , 1000grain weight, straw yield, grain yield, and protein %. Efforts are hardly exerted to enhance wheat productivity per unit area through creating new, highly productive cultivars that consume low water.…”
Section: Introductionmentioning
confidence: 99%